Microbiological and Clinical Effects of a Proanthocyanidin-enriched Extract from Rumex acetosa in Periodontally Healthy Carriers of Porphyromonas gingivalis: a Randomized Controlled Pilot Study - Selbach, Sabine; Klocke, Astrid; Peters, Ulrike; Beckert, Sabine; Watt, Rory Munro; Tong, Raymond; Flemmig, Thomas Frank; Hensel, Andreas; Beikler, Thomas (Planta medica, 2023)
significantly inhibits the adhesion of ( ) to eukaryotic host cells . The objective of this randomized placebo-controlled pilot-trial was to analyze effects of a mouth rinse containing 0.8% (w/w) of a quantified proanthocyanidin-enriched extract from (RA1) on microbiological, clinical, and cytological parameters in systemically healthy individuals without history of periodontitis, harboring intraorally. 35 subjects received a supragingival debridement (SD) followed by mouth rinsing (3 times daily) with either RA1 mouth rinse solution (test) or placebo (control) for 7 days as adjunct to routine oral hygiene. Supragingival biofilm samples were taken at screening visit, baseline (BL), 2, 4, 7 and 14 days after SD. and 11 other oral microorganisms were detected and quantified by rtPCR. Changes in the oral microbiota composition of one test and one control subject were assessed via high throughput 16S rRNS gene amplicon sequencing. Approximal Plaque Index (API) and the modified Sulcular Bleeding Index (SBI) were assessed at BL, 7- and 14-days following SD. Brush biopsies were taken at BL and 14 d following SD. Intergroup comparisons revealed no significant microbiological, cytological, and clinical differences at any timepoint. However, a significant reduction in SBI at day 14 ( = 0.003) and API at day 7 ( = 0.02) and day 14 ( = 0.009) was found in the test group by intragroup comparison. No severe adverse events were observed. The results indicate that RA1 mouth rinse is safe but does not seem to inhibit colonization of or improve periodontal health following SD.